2002
DOI: 10.1086/342226
|View full text |Cite
|
Sign up to set email alerts
|

The Bright Gamma‐Ray Burst of 2000 February 10: A Case Study of an Optically Dark Gamma‐Ray Burst

Abstract: The gamma-ray burst GRB 000210 had the highest γ-ray peak flux of any event localized by BeppoSAX as yet but it did not have a detected optical afterglow, despite prompt and deep searches down to R lim ≈ 23.5. It is therefore one of the events recently classified as dark GRBs, whose origin is still unclear.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 61 publications
8
92
0
2
Order By: Relevance
“…Moreover, small extinction values do not exclude the possibility that the GRBs themselves are located in more dusty and higher density environments, such as embedded in molecular clouds which has been suggested through analyses of X-ray afterglows. This was discussed for the case of the GRB 000210 host galaxy, where a large N H was inferred (Piro et al 2002), while the galaxy itself shows a small global extinction (see Table 2; and Gorosabel et al 2003a). However, if the regions of star formation where GRBs occur are small and not numerous, this will not have a large effect on the overall SEDs of the hosts.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, small extinction values do not exclude the possibility that the GRBs themselves are located in more dusty and higher density environments, such as embedded in molecular clouds which has been suggested through analyses of X-ray afterglows. This was discussed for the case of the GRB 000210 host galaxy, where a large N H was inferred (Piro et al 2002), while the galaxy itself shows a small global extinction (see Table 2; and Gorosabel et al 2003a). However, if the regions of star formation where GRBs occur are small and not numerous, this will not have a large effect on the overall SEDs of the hosts.…”
Section: Discussionmentioning
confidence: 90%
“…Since GRB 990506 is one of only a handful of well-studied dark bursts (also including GRB 000210, Piro et al 2002;and GRB 970828, Djorgovski et al 2001) the measurement of a redshift near the median of other long-duration bursts may suggest a common progenitor population. This emerging trend of similar redshift distributions will almost certainly be testable with the advent of systematic absorption redshift determinations for Swift bursts.…”
Section: Discussionmentioning
confidence: 99%
“…After a putative host has been identified, the observations can constrain not only the redshift but may also help to explain the optical dimness of the afterglow Several studies of individual events have already found that dust extinction in the corresponding GRBHs was the main reason for the optical dimness of some events (e.g., Piro et al 2002;Gorosabel et al 2003;Levan et al 2006;Berger et al 2007;Küpcü Yoldaş et al 2010;Krühler et al 2011). This conclusion then naturally leads to the question of whether extinction by cosmic dust can explain the entire ensemble of optically dark bursts or whether their high redshifts (seen as Lyman dropouts) is also an important factor.…”
Section: Bursts With Optically Undetected Afterglowsmentioning
confidence: 99%